Associations between Kynurenine pathway metabolites and cognitive dysfunction in major depressive disorder - Yingying Pan; Peiwei Xu; Xueli Sun (PLoS ONE, 2025)
This research sought to investigate the relationship between cognitive impairment and kynurenine pathway metabolites in individuals diagnosed with major depressive disorder (MDD). A total of 67 patients diagnosed with MDD and 61 healthy controls (HC) were enrolled in this study. Cognitive function was assessed utilizing the MATRICS Consensus Cognitive Battery. Plasma levels of tryptophan (TRP), kynurenine (KYN), kynurenic acid (KYNA), and quinolinic acid (QUIN) were quantified by liquid chromatography-tandem mass spectrometry. Subsequently, we examined the potential associations between metabolites of the KYN pathway and cognitive dysfunction. MDD patients exhibited significantly poorer performance across all cognitive domains, including processing speed, attention/vigilance, working memory, verbal learning, visual learning, reasoning and problem-solving, and social cognition. Inter-group comparisons indicated that levels of KYN, QUIN, and the KYN/TRP ratio in MDD patients were significantly lower than those in HC, whereas KYNA and the KYNA/QUIN ratio were significantly higher. In MDD patients, a negative correlation was observed between KYN levels and working memory (r = −0.302, p = 0.020), and the KYN/TRP ratio was also negatively correlated with working memory (r = −0.307, p = 0.018). Our findings indicate that impaired working memory in MDD is correlated with increased KYN levels and KYN/TRP ratio. This suggests that the KYN pathway may play a role in the pathological mechanisms underlying neurocognitive dysfunction, particularly working memory deficits, in MDD.